Plasticizer effect on the properties of biodegradable blend film from rice starch-chitosan - Thawien Bourtoom (Songklanakarin Journal of Science and Technology (SJST), 2008)
The properties of biodegradable blend film from rice starch-chitosan with different plasticizers were determined. Three plasticizers comprising sorbitol (SOR), glycerol (GLY) and polyethylene glycol (PEG) were studied over a range of concentration from 20 to 60%. Increasing concentration of these plasticizers resulted in decreased tensile strength (TS) concomitant with an increase in elongation at break (E), water vapor permeability (WVP) and film solubility (FS). SOR plasticized films were the most brittle, with the highest tensile strength (TS, 26.06 MPa). However, its effect on WVP was low (5.45 g.mm/m2.day.kPa). In contrast, GLY and PEG plasticized films had a flexible structure contradictory to a low TS (14.31MPa and 16.14MPa, respectively) providing a high WVP (14.52 g.mm/m2.day.kPa and 14.69 g.mm/m2.day.kPa, respectively). SOR plasticized films, demonstrated little higher FS compared to PEG and GLY plasticized films but not significant different (p<0.05). The color of biodegradable blend film from rice starch-chitosan was more affected by the concentration of the plasticizer used than by its type. Nine moisture sorption models were applied to experimental data. Moisture content of the film increased at elevated water activity. The time to reach equilibrium moisture content (EMC) was about 20-24 days at lower humidity and 13-16 days at higher humidities. The EMC of glycerol and sorbitol rice starchchitosan biodegradable blend films showed a logarithmic increase at above 0.59 aw and reached the highest moisture content of 51.46% and 42.97 % at 0.95 aw, whereas PEG rice starch-chitosan biodegradable blend films did not show much increase in moisture content.